The construction of the trans subject in the social voices that cross the medical discourse in The danish girl - Sousa, Claudemir [UNESP] (Univ Estado Rio Grande Norte, 2020)
This article analyzes the construction of the trans subject in the film The Danish girl (2015), by Torn Hopper, on the social voices that cross the medical discourse present in it. Our discussions are anchored on the assumptions of the Dialogic Discourse Analysis, centered on Mikhail Bakhtin's works and his commentators, mobilizing, above all, the concept of social voices, and on the studies of gender and sexuality by Butler (2000), Louro (2001) and other interlocutors. The methodology used has a qualitative approach, with a descriptive and interpretative nature, based on the Bakhtinian proposal of a dialogical analysis of utterances, which means establishing relationships with the theoretical discussions that situate sexuality in the history. We concluded that the clashes between the social voices that cross the medical discourse present in the film build the trans subject in ambivalent paths, which contribute either to the negation and treatment of gender identity or to their acceptance and adjustment to the desire.
Keywords: Dialogic Discourse Analysis; Trans subject; Social voices